PENERAPAN MEDIA CANVA TERHADAP PENGEMBANGAN LITERASI MENULIS SISWA MELALUI PROYEK MADING SEKOLAH DI SMK AL-KARIMIYYAH SUMENEP - Siti Sofa Riskianti; Listiani; Ianatul Musammita; Gita Shevania; Ainur Rahman; Yeni Puji Astuti (Jurnal Pendidikan Dewantara, 2026)
This study aims to describe the impact of implementing Canva on the development of students' writing literacy through a wall magazine project at SMK Al-Karimiyyah Sumenep. This research is crucial due to students' lack of ability and motivation in writing. The method used is descriptive qualitative, with data collected through observation, interviews, and documentation of student work. The subjects were 10th and 11th grade students majoring in Agribusiness and Agricultural Product Processing (APHP) and Motorcycle Engineering (TSM). Data analysis consisted of three stages: data reduction, data presentation, and conclusion drawing. The results indicate that Canva provides a creative space for students, increases motivation, and enhances their interest in writing skills. Canva has proven effective as an innovative tool in developing students' writing literacy through a wall magazine project.